Unexpected finding of uniparental disomy mosaicism in term placentas: Is it a common feature in trisomic placentas?. (27th September 2018) - Van Opstal, Diane; Diderich, Karin E.M.; Joosten, Marieke; Govaerts, Lutgarde C.P.; Polak, Joke; Boter, Marjan; Saris, Jasper J.; Cheung, Wai Yee; van Veen, Stefanie; van de Helm, Robert; Go, Attie T.J.I.; Knapen, Maarten F.C.M.; et al.
Abstract: Objective: Non‐invasive prenatal testing (NIPT) detects placental chromosome aberrations. When amniocentesis reveals a normal karyotype, confined placental mosaicism (CPM) may be assumed. In order to confirm this, placental cytogenetic studies were performed. Method: NIPT was conducted in the course of the Dutch TRIDENT study. Placentas of 10 cases with NIPT results indicating an autosomal trisomy and showing a normal ( N  = 9) or low mosaic karyotype ( N  = 1) in amniotic fluid (AF) were investigated. The cytotrophoblast as well as the mesenchymal core of two to four placental chorionic villi biopsies were studied with single nucleotide polymorphism (SNP) array. Clinical outcome data were collected. Results: In 10/10 cases, CPM was proven. In 3/10 cases trisomy/uniparental disomy (UPD)/biparental disomy (BPD) mosaicism was discovered. In 2/3 cases, all three cell lines were present in the placenta, whereas BPD was found in AF. In 1/3 cases trisomy 22/UPD22 was present in AF while trisomy 22/BPD22 mosaicism was found in the placenta. Five of 10 pregnancies were affected with pre‐eclampsia, low birth weight, preterm delivery, and/or congenital malformations. Conclusion: The presence of trisomy/UPD/BPD mosaicism in 3/10 cases that we investigated proves that trisomic zygote rescue may involve multiple rescue events during early embryogenesis. UPD mosaicism, when present in crucial fetal tissues, may explain the abnormal phenotype in undiagnosed cases. Abstract : What's already known about this topic? Trisomic zygote rescue is the main mechanism for uniparental disomy (UPD) formation. Confined placental mosaicism (CPM) is the major source of discordant NIPT results. CPM is associated with a risk for adverse pregnancy outcome. What does this study add? Trisomic zygote rescue may involve multiple rescue events based on the co‐occurrence of a trisomy‐, UPD‐, and BPD‐cell line in half of the rescued cases as revealed by placental studies.